The Effect Of Health Education On Groom And Bride Candidates’ Attitude And Belief In Tarakan City - Muhammad Aris; Syamsiah Syam; Asma (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Abstract Background.The attitude and belief of groom and bride candidates on exclusive breastfeeding were still low. Objective.This study aimed at examining the effect of exclusive breastfeeding module on the attitude and belief of groom and bride candidates at Tarakan City. Method. This study applied quantitative approach with pre-test post-test. The subjects of this research were groom and bride candidates who attended pre-marriage counseling at Ministry of Religion office of Tarakan City where the number of sample were 100 respondents. The distribution of exclusive breastfeeding module was done after pre-test to measure the groom and bride candidates’ attitude towards exclusive breastfeeding. The data analysis was done using T-test of Paired Samples Test. Findings. The characteristics of male respondents in Module Reading group were generally aged from 25 to 30 years old (52%) and those who belonged to Lecture Listening group were generally aged from 20 to 24 years old and 25 to 30 years old (32% and 32%). Female respondents in Module Reading group and Lecture Listening group were generally aged from 25 to 29 years old (40%) and 20 to 24 years old (56%). The attitude and belief of the male respondents in all groups after intervention were, in general, statistically meaningful to the value of p<0.05. The attitude of female respondents in module reading group was not meaningful while the belief of female respondents in Lecture Listening group was also not meaningful. Conclusion Health Education can improve the attitude and belief of male respondents on exclusive breastfeeding while the attitude and belief of female respondents in all groups were different from the male respondents’ after the intervention. It is suggested that exclusive breastfeeding materials are given to groom and bride candidates. Key words: Attitude and Belief, Groom and Bride Candidates, Exclusive Breastfeeding